Network pharmacology analysis and experimental verification of the antitumor effect and molecular mechanism of isocryptomerin on HepG2 cells - Cao, Jing‐Long; Li, Shu‐Mei; Tang, Yan‐Jun; Hou, Wen‐Shuang; Wang, An‐Qi; Li, Tian‐Zhu; Jin, Cheng‐Hao (Drug development research, 2024)
Isocryptomerin (ISO) is a flavonoid isolated from the natural medicine Selaginellae Herba, which has various pharmacological activities. This study investigated the antitumor effect and underlying molecular mechanism of ISO on hepatocellular carcinoma (HCC) HepG2 cells. The cell viability assay revealed that ISO has a considerable killing effect on HCC cell lines. The apoptosis assay showed that ISO induced mitochondria‐dependent apoptosis through the Bad/cyto‐c/cleaved (cle)‐caspase‐3/cleaved (cle)‐PARP pathway. The network pharmacological analysis found 13 key target genes, and epidermal growth factor receptor (EGFR), AKT, mitogen‐activated protein kinase (MAPK), and reactive oxygen species (ROS) signaling pathways were strongly associated with ISO against HCC. Further verification of the results showed that ISO induced apoptosis by increasing p‐p38 and p‐JNK expression and decreasing p‐EGFR, p‐SRC, p‐ERK, and p‐STAT3 expression. Furthermore, ISO induced G0/G1 phase arrest by downregulating p‐AKT, Cyclin D, and CDK 4 expression and upregulating p21 and p27 expression in HepG2 cells. Moreover, ISO inhibited HepG2 cell migration by decreasing p‐GSK‐3β, β‐catenin, and N‐cadherin expression and increasing E‐cadherin expression. Additionally, ISO promoted ROS accumulation in HepG2 cells, and ISO‐induced apoptosis, arrest cell cycle, and inhibition of migration were reversed by an ROS scavenger, N‐acetyl‐ l‐cysteine. Overall, ISO induced cell apoptosis and cell cycle arrest and inhibited cell migration by ROS‐mediated EGFR, AKT, and MAPK signaling pathways in HepG2 cells.